2013
DOI: 10.1089/chi.2012.0096
|View full text |Cite
|
Sign up to set email alerts
|

Underestimation of Weight Status in Californian Adolescents

Abstract: Identification of individuals at increased odds of underestimating their weight status may be important in developing and targeting appropriate counseling and interventions to ameliorate long-term health risks of excess weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It has been indicated that either overestimation or underestimation of body weight is correlated with health issues in adolescents, including depression and certain psychological conditions [ 15 , 16 , 17 ]. This may in turn affect adolescents’ weight management behaviors [ 18 , 19 ]. In particular, non-overweight adolescents who overestimate their body size may experience body dissatisfaction, leading to greater risk for disordered eating and eating disorders [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been indicated that either overestimation or underestimation of body weight is correlated with health issues in adolescents, including depression and certain psychological conditions [ 15 , 16 , 17 ]. This may in turn affect adolescents’ weight management behaviors [ 18 , 19 ]. In particular, non-overweight adolescents who overestimate their body size may experience body dissatisfaction, leading to greater risk for disordered eating and eating disorders [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…1, 2 Among non-overweight and overweight adolescents, both overestimation and underestimation of weight status are associated with adverse outcomes such as depressive symptoms and other psychological problems, 35 and subsequently may influence weight management behaviors. 6, 7 In particular, non-overweight adolescents who overestimate their body size may experience body dissatisfaction leading to greater risk for disordered eating and eating disorders. 2 Conversely, overweight adolescents who underestimate their body size may be less motivated to reduce body fat, thus increasing chronic disease risk.…”
Section: Introductionmentioning
confidence: 99%